Diagnostics of School Involvement of Learners Included in the Practice of Participatory Budgeting - Boris V. Kupriyanov (National Research Mordova State University, 2023)
Introduction. The research problem is to determine the measurable results of using a separate educational practice (school initiative budgeting). The purpose of the article is to reveal the relationship between the level of school involvement of students and the intensity of their participation in the practice of school initiative budgeting. Materials and Methods. In 2021-2022 An empirical study was conducted in seven educational institutions of the Khanty-Mansi Autonomous Okrug - Yugra, in which 182 schoolchildren took part. The study included measurements of school involvement in 11 parameters (activities, communication and relationships) of learners who, to varying degrees of activity, participate in school initiative budgeting. Engagement study methodology was used ‒ a modified Gallup Q12 questionnaire, an interview, a questionnaire for schoolchildren and a questionnaire for teachers. Results. An authorʼs model of school involvement, a program for diagnosing school involvement and active participation in school initiative budgeting have been developed. Statistical processing of the measurements made it possible to assert that the intensity of participation in school initiative budgeting correlates with the level of school involvement of students, the more actively a student participates in school initiative budgeting, the higher the degree of his school involvement. Discussion and Conclusion. The presented results testify to the prospects of using the model and scheme for diagnosing school involvement. The materials of the article are of interest in the context of determining the results of the implementation of school initiative budgeting in the practice of Russian educational organizations and school participatory budgeting abroad.